The experience and rehabilitation of patients operated on external genital endometriosis - V. A. Krutova; T. G. Melkoniants; N. A. Kravtsova; E. G. Pirozhnik; L. V. Makarenko; A. V. Ephimenko; I. I. Kravtsov; A. A. Ordokova; A. N. Titova (Кубанский научный медицинский вестник, 2016)
During present research, 216 patients with external genital endometriosis were examined. Examined women had been suffering from complaints (pelvic pain, dyspareunia, psycho-emotional disorders) from 1.5 to 19 years. The influence of these methods of rehabilitation was monitored on parameters of life quality and intensity of pain before and after treatment. Therapy included use of dienogest 2 mg or ethynilestradiol 30 mсg/dienogest 2 mg with or without radonotherapy. Positive effects of all three methods were revealed. After treatment amount of women, still complaining of pelvic pain reduced to 12.0-30.6%. In comparison application of dienogest 2 mg and radon appears to be more effective.